Construction of a Novel Liver-Targeting Fusion Interferon by Incorporation of a Plasmodium Region I-Plus Peptide. (19th January 2014) - Lu, Xuemei; Jin, Xiaobao; Huang, Yanting; Wang, Jie; Shen, Juan; Chu, Fujiang; Mei, Hanfang; Ma, Yan; Zhu, Jiayong
Abstract : Interferon alpha (IFN α ) exerts a multiplicity of biological actions including antiviral, immunomodulatory, and antiproliferative effects. Administration of IFN α is the current treatment for chronic hepatitis B; however, therapy outcome has not been completely satisfactory. The systemic effects of IFN α may account for its low in vivo biological activity and multiple adverse events. The purpose of this study was to design a novel liver-targeting fusion interferon (IFN-CSP) by fusing IFN α 2b with a Plasmodium region I-plus peptide, thus targeting the drug specifically to the liver. The DNA sequence encoding IFN-CSP was constructed using improved splicing by overlapping extension-PCR method, and then cloned into the pET-21b vector for protein expression in E. coli BL21 (DE3). The recombinant protein was expressed as a His-tagged protein and purified using a combination of Ni affinity and HiTrap affinity chromatography at a purity of over 95%. The final yield of biologically active IFN-CSP was up to 270 mg/L culture. The purified recombinant protein showed anti-HBV activity and liver-targeting potentiality in vitro . These data suggests that the novel fusion interferon IFN-CSP may be an excellent candidate as a liver-targeting anti-HBV agent.